Asterisk Gateway Interface 1.4 and 1.6 programming : design and develop Asterisk-based VoIP telephony platforms and services using PHP and PHPAGI /: design and develop Asterisk-based VoIP telephony platforms and services using PHP and PHPAGI. (2009) - Unknown
No abstract available